HPTLC Finger Printing Profile Of Drynaria Quercifolia (L.) J. Sm. With Biomarker Naringin - Raj, Greshma P; Shincymol, V V; Ansary, P Y; Oommen, Sara Moncy (International Research Journal of Ayurveda & Yoga, 2021)
Drynaria quercifolia (L.) J. Sm. is a common and safe medicinal fern of tropical climate, used by Ayurvedic physicians of Kerala and tribal peoples in different parts of the country for various ailments with inflammation. But, to get a desired therapeutic effect the drug must be genuine with good quality. Authentication and quality of plants can be accurately done by doing HPTLC fingerprints with biomarker. Development of HPTLC finger printing profile of aqueous extract of rhizome of the plant with biomarker naringin was the aim of this study. Precoated silica gel 60 F254 was the stationary phase and ethyl acetate, formic acid, acetic acid, water in the ratio -1.5:1.1:1.1:0.1 was the mobile phase used for this purpose. After derivatization with methanolic sulphuric-10%, TLC plates were viewed at UV 366 nm and in visible light and densitometric profile were developed at 590 nm. At 590 nm, chromatogram of the aqueous extract of the drug showed 4 peaks and the 3rd peak was found to be homologous to the chromatogram of naringin. Thus the study revealed the identification as well as genuineness of the plant and has shown the potency of the drug as an anti-inflammatory agent.